The Relationship between Psalms 25 and 37 - Botha, Phil J. (Old Testament Essays, 2007)
The similarities between Psalms 25 and 37 are investigated. This pertains to the vocabulary and expressions used in the two psalms, their alphabetic form, and the theological point of view expressed. It is argued that the similarities between them should be attributed to the fact that they were written at more or less the same time by the same group of persons. The authors considered Proverbs, the major prophets, and an early form of the Psalter as authoritative material containing the Torah of Yahweh, and held on to the conviction that righteousness in the form of humility, patience, doing what is right, and seeking shelter with Yahweh will be rewarded with eventual control over the Promised Land.
free